ANALISIS KESULITAN BELAJAR SISWA MADRASAH IBTIDAIYAH DALAM MEMAHAMI SOAL CERITA PADA MATERI PECAHAN - Ahmad Ahmad (JURNAL MAHASANTRI, 2021)
Abstract: The purpose of this study is to find out how the mistakes faced by students madrsaha ibtidaiyah grade IV Nurul Yaqin Kelanjur against fractional material in the form of story problems. Meted research used in this study is a shortness of kulaitatai. Data collection method is by observation, interview and documentation. The source of the data is the head of madrasah, mathematics teacher and grade IV students in MI Nurul yaqin Kelanjur. External factors are: How to teach teachers who are still monotonous and the lack of reference books for students because the school does not yet have a library. While the internal factors are: Students do not master the basic operations of fractions, difficulty understanding problems in the story and the unavailable props about fractional material. To overcome these difficulties can be done by using props when explaining the story of fractional material, multiplying the practice of working on the story on fractional material, giving explanations using concrete objects, and making story problems with communicative language. Keywords: difficulty balajar and bilagan fractions